CIAT's role in international snap bean research - Kornegay, Julia L. (International Center for Tropical Agriculture, 1990)
Snap bean research at CIAT is relatively new. It began in 1982 as a student thesis project to evaluate snap bean germplasm. Later, new introductions were received and sources of resistance to rust were identified. A modest crossing program was initiated and the first advanced lines entered the VEF nursery in 1985. At CIAT all snap bean research is carried out within the Bean Program. Much of the research conducted on common bean is directly applicable to snap beans. The demand for new snap bean technology is high. The majority of the varieties being planted in the tropics come from Europe and North America and are susceptible to many tropical bean diseases and insect pests. Pesticide abuse is becoming a major problem. To provide some solutions to these problems, CIAT will continue and even expand research on the genetic improvement of snap beans during the next five years. Improved breeding lines will be a critical component in the on-farm testing of IPM technologies. National agricultural research institutions and private industries will be expected to be the leaders in developing snap bean technologies for the tropics, working in a network together with CIAT. (AS)